Buprenorphine reduces methamphetamine intake and drug seeking behavior via activating nociceptin/orphanin FQ peptide receptor in rats - Wang, Fangmin; Shen, Wenwen; Cai, Yujia; Zhang, Xin; Du, Han; Lai, Miaojun; Liu, Huifen; Kohli, Evelyne; Zhou, Wenhua (Frontiers in Psychiatry, 2022)
Buprenorphine, which has been approved for the treatment of opioid dependence, reduces cocaine consumption by co-activating μ-opioid receptors and nociceptin/orphanin FQ peptide (NOP) receptors. However, the role of buprenorphine in methamphetamine (METH) reinforcement and drug-seeking behavior remains unclear. This study investigated the effects of buprenorphine on METH self-administration and reinstatement of METH-seeking behavior in rats. We found that buprenorphine pretreatment had an inhibitory effect on METH self-administration behavior, and that buprenorphine at a dose of 0.3 mg/kg could inhibit motivation to respond for METH. Pretreatment with the NOP receptor antagonist thienorphine (0.5 mg/kg) or SB-612111 (1 mg/kg) could reverse the inhibitory effect of buprenorphine (0.1 mg/kg) on the METH self-administration. Moreover, treatment with buprenorphine (0.1 mg/kg and 0.3 mg/kg) significantly reduced the drug-seeking behavior induced by context or by METH priming, butpriming but failed to reduce the drug-seeking behavior induced by conditional cues. Additionally, the NOP receptor antagonist SB-612111 reversed the inhibitory action of buprenorphine on the drug-seeking behavior induced by METH priming. The results demonstrated that buprenorphine reduced either METH intake or the drug-seeking behavior by activating NOP receptors, providing empirical evidence for the clinical use of buprenorphine in the treatment of METH relapse and addiction.